Academic stress and life satisfaction as social sustainability among university students - Balan Rathakrishnan; Soon Singh Bikar Singh; Azizi Yahaya; Mohammad Rahim Kamaluddin; Fauziah Ibrahim; Zaizul Ab Rahman (Institute of Advanced Engineering and Science, 2022)
This study was conducted to determine the relationship between academic stress and life satisfaction among university students in Sabah, Malaysia. A total of 400 students were selected as respondents and data were collected using questionnaires. Academic stress was measured using the Perception of Academic Stress Scale (PAS), which has four subscales: i) Performance stress; ii) Workload perception of workload and examinations; iii) Academic self-perception; and iv) Time constraints. Meanwhile, the Satisfaction with Life Scale was used to study student’s life satisfaction. The data obtained were analyzed using Pearson correlation and t-test. The results showed that performance stress is negatively associated with life satisfaction, while academic self-perception is positively associated with life satisfaction. The result also showed that perception of workload and examinations and time constraints not associated with life satisfaction. All in all, academic self-perception and performance stress have an association with life satisfaction.